Multi-time scale rolling optimal dispatch for microgrids with high renewable penetration - Yeo, Wen Hui (Nanyang Technological University, 2023)
Renewable energy (RE) sources are known to have high intermittency and are unreliable energy sources for power systems. Measures have been taken to improve reliability, such as incorporation of energy storage (ES) systems, and backup diesel engine (DE) generators. These measures require customised parameters for a specific microgrid (MG). The day-ahead scheduling and intraday real-time dispatch data for all parameters of a microgrid, which are photovoltaic (PV) generation data, state of charge of ES, charging and discharging power of ES, price of electricity, buying and selling power of ES and lastly, power generation of DE, are considered. Using real-time data measured from a microgrid in Clean Energy Research Lab (CERL), NTU, the trends of the parameters have been studied to compare the impact to the day-ahead scheduling data, which is used for constant improvements of MG parameters to ensure reliability and cost-effectiveness.